Design and Control of Intelligent Robotic Systems - Liu, Dikai.; Wang, Lingfeng.; Tan, Kay Chen. (Studies in Computational Intelligence,, 2009)
With the increasing applications of intelligent robotic systems in various fields, the design and control of these systems have increasingly attracted interest from researchers. This edited book entitled Design and Control of Intelligent Robotic Systems in the book series of Studies in Computational Intelligence is a collection of some advanced research on design and control of intelligent robots. The works presented range in scope from design methodologies to robot development. Various design approaches and algorithms, such as evolutionary computation, neural networks, fuzzy logic, learning, etc. are included and most studies reported in this book have been implemented in physical systems. The intended readers of this edited book are engineers, researchers, senior undergraduates, and graduate students who are interested in the field of design and control of intelligent robotic systems.